Perbandingan Estimasi Cadangan Klaim dengan Metode Classical Chain Ladder dan Bornhuetter-Double Chain Ladder - Krisdiantha Krisdiantha; M. Jibril Khalifatullah; Tione Daffaxa Dumamika; Lienda Noviyanti (Department of Mathematics, Hasanuddin University, 2023)
In the world of insurance, insurance companies need to back up claims to ensure that the company can cover expenses resulting from filing claims from policyholders. Claim reserves represent the estimated value of claim payments in the future, where there are differences in the estimated and actual value of claim payments. Errors in predicting claim reserves will result in inaccuracies and disrupt the insurance company's financial stability. There are several ways to estimate claim reserves, one of the most common methods is using a Chain Ladder. However, the Chain Ladder method is very susceptible to outliers, so another method is needed to estimate claims reserves that are more accurate. This study discusses the comparison between the Chain Ladder method and one of the development methods, namely Bornhuetter-Double Chain Ladder in estimating claim reserves. The Bornhuetter-Double Chain Ladder method uses data on claims that have occurred as a whole, the amount of claims that have been paid, and the number of claims that have occurred. Based on the research results, it can be concluded that the Bornhuetter-Double Chain Ladder method is capable of producing more stable and accurate claim reserves compared to the Chain Ladder method.